Analisis Hubungan Kualitas Air Minum Terhadap Kejadian Diare Anak di Kelurahan Karyajaya Kota Palembang - Melvani, Rizcita Prilia; Novianti, Leni (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Sanitation is a health effort carried out by maintaining and protecting the cleanliness of the environment. Indonesia is currently still facing big challenges in realizing access to sanitation facilities, especially access to clean water which people use for their daily needs, for eating and drinking. As the rate of human growth increases, the need for clean water and drinking water also increases. The increase in population needs to be balanced with an increase in the amount of quality water. Good water quality must also be considered in meeting daily needs, because clean water quality will affect health, especially clean water and drinking water used in Karyajaya Village, Palembang City using quantitative research methods. The number of samples used in this research was 60 households with children. The research instruments were questionnaires and drinking water measurement tools. Bivariate analysis used the chi square test (?= 0.05). The research results showed that there was a significant relationship between the quality of drinking water and the incidence of children's diarrhea in Karya Jaya Village, Palembang City (p value = 0.044).